2023
DOI: 10.1108/bfj-02-2023-0092
|View full text |Cite
|
Sign up to set email alerts
|

Reducing food waste by simply measuring it: insights from interventions to reduce household food waste

Gabriel Jäger Ramos,
João Augusto Rossi Borges,
Carla Heloisa de Faria Domingues
et al.

Abstract: PurposeOvercooking and overbuying are two main causes of food waste in households. Therefore, this study tests whether two interventions, aimed at cooking planning versus purchasing planning, can reduce food waste in households by using self-report direct measurements. Because measuring household food waste can impact how much food is wasted, the effects of the mere measurement of household food waste over time were assessed as well.Design/methodology/approachA sample of 80 households was distributed into thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Of the grouped studies, all but one [56] incorporated a control group in the study design, reducing confounding external factors, and enabling a change in behaviour to be attributable to the success of an intervention [44,79]. Recent literature has indicated that measurement may impact on behaviour, and thus differences between the control group and treatment group are necessary to indicate if an intervention works, if all groups show a reduction in food waste post-test [13]. In Young, Russell, Robinson, and Barkemeyer's study [58], participants were placed in groups dependent on the prior self-reported awareness of campaign materials, thus it cannot be assumed that the participants were like-for-like across groups, as purposeful allocation renders the control group a quasicontrol [58,80].…”
Section: Treatment Group Allocationmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the grouped studies, all but one [56] incorporated a control group in the study design, reducing confounding external factors, and enabling a change in behaviour to be attributable to the success of an intervention [44,79]. Recent literature has indicated that measurement may impact on behaviour, and thus differences between the control group and treatment group are necessary to indicate if an intervention works, if all groups show a reduction in food waste post-test [13]. In Young, Russell, Robinson, and Barkemeyer's study [58], participants were placed in groups dependent on the prior self-reported awareness of campaign materials, thus it cannot be assumed that the participants were like-for-like across groups, as purposeful allocation renders the control group a quasicontrol [58,80].…”
Section: Treatment Group Allocationmentioning
confidence: 99%
“…The review results should be interpreted with the focused scope in mind of adult consumers within the household in countries that tend to generate more food waste. The following notable studies may be relevant for similar reviews with widened PICOS parameters: Davenport et al, 2019 [92]; Giordano et al, 2019 [25]; Neff et al, 2019 [93]; Revilla and Salet, 2018 [94]; Russell et al, 2017 [60]; Septianto et al, 2020 [95]; van Dooren et al, 2020 [96]; and Ramos et al 2023 [13]. To the authors' knowledge, there are no missing results from this review that fit the inclusion and exclusion criteria or bias due to missing results [36].…”
Section: Limitations and Study Risk Of Bias Assessmentmentioning
confidence: 99%
See 2 more Smart Citations